2018
DOI: 10.1002/stc.2261
|View full text |Cite
|
Sign up to set email alerts
|

Vibration control in wind turbines to achieve desired system-level performance under single and multiple hazard loadings

Abstract: The increased demand in energy and the need for sustainable and renewable sources of electricity in hazardous environments with significantly growing population yields the installation of more wind turbines in these areas. In addition, the technological development in material and construction methods has led to the building of taller and more flexible turbines, with inherent low structural damping. Installing modern wind turbines in offshore harsh environments or seismic prone areas can cause an increment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 85 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…e structure considered in this study is a 76-story benchmark building, which is very sensitive to wind [33][34][35][36]. Detailed information of the building can be found in reference [33,35]. Different control schemes considered in this study are illustrated in Figure 1.…”
Section: Benchmark Building With/without Tmdsmentioning
confidence: 99%
See 2 more Smart Citations
“…e structure considered in this study is a 76-story benchmark building, which is very sensitive to wind [33][34][35][36]. Detailed information of the building can be found in reference [33,35]. Different control schemes considered in this study are illustrated in Figure 1.…”
Section: Benchmark Building With/without Tmdsmentioning
confidence: 99%
“…Chapain and Aly [32] reported that viscous dampers showed their potential to enhance dynamic performance of buildings under multiple hazards. Earlier to this, Rezaee and Aly [33,34] reported that semiactive controllers were quite effective in vibration mitigation of a wind turbine subjected to multiple hazards.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Tuned mass dampers (TMDs) are one of the common control methods used for response mitigation of structures under dynamic loadings. Their applications in various situations and loads have been addressed by several researchers [1][2][3][4][5][6][7]. As single tuned mass dampers (STMDs) became popular, a more practical solution, for example, by distributing TMD mass over the structure is being investigated in recent times [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although its damping force is generated passively by the motion with the structure, the control device can use external energy to adjust its damping force. Typical devices are magneto‐rheological dampers . Passive control is a method consuming no external energy, and its damping force is generated passively by the vibration deformation with the structure.…”
Section: Introductionmentioning
confidence: 99%